On the Occurrence of Tropidia curculigoides Lindl. at Golatappar, Dehra Dun - Dev, Som; Arora, C. M. (Indian Forester, 1971)
Tropidia curculigoides Lindl. A terrestrial orchid reported previously from Sikkim, Assam and Burma, has now been recorded from Golatappar Swamp forest, Dehra Dun.